2018
DOI: 10.15446/revfacmed.v66n4.63743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of surgical complications in gynecological surgery at the Hospital Universitario San José in Popayán, Colombia. 2015

Abstract: Introduction: Every surgery has risk of complications; prognosis depends on prompt diagnosis and timely management.Objective: To determine the prevalence of surgical complications in gynecological surgery in a tertiary care hospital and to explore associated factors.Materials and methods: Prevalence study with secondary analysis of medical records of patients who underwent scheduled gynecological surgery. The outcome variable was complications reported during a period of less than 30 days. The universe was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
4
14
2
Order By: Relevance
“…The average duration of hospital stay after surgery was 10.79 + 7.91 days, and the mean duration of hospital stay was the longest in abdominal surgeries (11.5 days), followed by vaginal (7.5 days), and laparoscopic surgeries (7.3 days) due to complications. Compared to the study by Ortiz-Martínez et al [ 4 ], where the reported prevalence of general complications following gynaecological surgery was 3.8%, our study had a higher complication rate. This could be explained by the fact that we included only major gynaecological procedures, unlike Ortiz-Martínez et al who also analysed cases involving tubal ligation and curettage.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…The average duration of hospital stay after surgery was 10.79 + 7.91 days, and the mean duration of hospital stay was the longest in abdominal surgeries (11.5 days), followed by vaginal (7.5 days), and laparoscopic surgeries (7.3 days) due to complications. Compared to the study by Ortiz-Martínez et al [ 4 ], where the reported prevalence of general complications following gynaecological surgery was 3.8%, our study had a higher complication rate. This could be explained by the fact that we included only major gynaecological procedures, unlike Ortiz-Martínez et al who also analysed cases involving tubal ligation and curettage.…”
Section: Discussioncontrasting
confidence: 88%
“…The prevalence of SSI varies among different studies. Ortiz-Martínez et al [ 4 ] and Barbosa et al [ 9 ] have reported a prevalence of 1.52% and 2.2% respectively, which are lower compared to our rates. Pathak et al [ 10 ] in their analysis of 1,173 cases involving both obstetric and gynaecological cases reported a 10.3% SSI rate following gynaecological surgeries, which aligns with our findings.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Complications may result from the proximity of the gynaecological organs to the urinary tract, bowel, nerves, and vasculature. A 3.8% overall prevalence rate of complications for gynaecological surgery was reported; 1.8% were major and 2% were minor complications [21]. To perform safe surgery, O&G doctors should have adequate surgical anatomy knowledge particularly in situations where anatomy is distorted by adhesions or surgical bleeding [22].…”
Section: Discussionmentioning
confidence: 99%